Microwave pyrolysis of oil palm shell for supercapacitor applications / Manoj Tripathi - Manoj , Tripathi (2016)
In the present work, a carbonaceous, porous oil palm shell (OPS) char with high thermal stability and low thermal conductivity has been synthesized using microwave pyrolysis technique. In comparison with conventional heating, microwave heating provides a rapid and uniform heating without suffering from high energy loss during the heating process. Process parameters such as microwave power, radiation time and N2 flow rate have been investigated and found to have a significant effect on the yield and BET surface area of OPS char. Central Composite Design (CCD) technique of Response Surface Methodology (RSM) is used to conduct the optimization study so as to get the optimized process conditions for the maximized yield and BET surface area of OPS char. Thermal, structural, elemental, compositional and dielectric characterization of the OPS char is carried out to check its utility as electrode material. Large BET surface area (265.9 m2/g) and porous nature (pore volume 1.28 cm3/g) of OPS char is helpful in the charge storage application. Furthermore, surface area analysis of OPS char has also revealed that microwave pyrolysis process has developed the micro pores within the OPS char which are clearly seen in the SEM images of OPS char. Thermogravimetric analysis showed that OPS char has a higher thermal stability temperature (355 °C) as compared to OPS (270 °C). OPS char is found to have a high carbon content (59.42 wt. %). Dielectric properties are found to be largely dependent upon microwave frequency and as well as on temperature. Dielectric characterization of OPS shows that penetration depth of microwave radiation with frequency 2450 MHz is lower than that of 915 MHz frequency by 11.6 % which imply that microwave radiation with frequency 2450 MHz are more suitable for the thermal treatment of OPS. OPS char is seen to have lower thermal conductivity and thermal diffusivity as compared to OPS (0.169 W/m-K & 0.124 mm2/s respectively for OPS char as compared to 0.199 W/m-K & 0.142 mm2/s respectively for OPS). Low thermal conductivity and thermal diffusivity suggests OPS char to be a good insulating material. Specific heat capacity of OPS char is higher than that of OPS. Based on all these results it is found that the synthesized OPS char has a large BET surface area, high carbon content, porous nature, higher thermal stability, low thermal conductivity along with high specific heat capacity. These properties are appropriate for its consideration as an electrode material. OPS char derived electrode is prepared and its charge storage capacity is determined using cyclic voltammetry. Specific capacitance of OPS char electrode is found to be 203.30 F/g which is comparable to the other biomass/ agricultural waste based char materials. Economically, it looks very attractive that by considering the OPS char synthesis cost to be $100/MT it is possible to reduce the charge storage cost to less than 0.0005 cent/F using its specific capacitance to be 203.30 F/g. Based on all the above mentioned results we propose that the OPS char synthesized in the optimized process conditions using the microwave pyrolysis has the potential to be considered as a supercapacitor electrode material